A facile and new preparation of crystalline Ag loaded TiO2 nanoparticles by a one-step method at room temperature. (August 2023) - Lin, Qingqing; Zhu, Yu; Wang, Qun; Huang, Yue; Zhou, Zhonghua
Highlights: Crystalline Ag is photoreduced on the crystal plane of rutile (101). Amorphous Ag is photoreduced on the crystal plane of anatase (101). The crystal plane of rutile (101) is the dominant plane for crystal Ag (111) precipitation. A facile and new one-step method at room temperature for the preparation of c-Ag/TiO2 NPs. Abstract: Crystalline Ag loaded TiO2 (c-Ag/TiO2 ) nanoparticles (NPs) has higher photocatalytic activity than amorphous Ag loaded TiO2 (a-Ag/TiO2 ) NPs, but its preparation usually requires multi steps and high temperatures. In this work, c-Ag/TiO2 NPs have been successfully prepared by one-step UV reduction at room temperature, using TiO2 (P25) and AgNO3 as raw materials. The phase, grain size, crystallinity and morphology of such c-Ag/TiO2 NPs have been analyzed by X-ray diffraction, element surface distribution and field emission transmission electron microscope. The crystal plane form of TiO2 is the main factor affecting the formation of c-Ag/TiO2 in the process of photoreduction of Ag + to Ag 0 on the surface of TiO2 at room temperature. Among the anatase and rutile phases of TiO2 (P25), rutile TiO2 (101) crystal plane is the predominant crystal plane for precipitation of crystalline Ag (111) to form c-Ag/TiO2 . Graphical abstract: Image, graphical abstract